Исследование влияния интервьюера на ответы респондента: результаты методического эксперимента - Мищенко, М. (Социология: теория, методы, маркетинг, 2004)
The essential role in research errors on electoral orientations is played by low sincerity of respondents. Although this idea has been discussed by sociologists for a rather long period of time, this influence has not been assessed experimentally. The methods experiment represented in the article makes it possible to determine how ways of interview may affect respondent's answers.